Keragaman Anggrek (Orchidaceae) di Kecamatan Purwodadi Kabupaten Musi Rawas, Provinsi Sumatera Selatan - Merti Triyanti; Harmoko Harmoko; Eva Apriyani (Jurnal Biologi Papua, 2022)
This study aims to determine the types of orchids in Purwodadi Subdistrict and Musi Rawas District, South Sumatra Province which have not been recorded in detail. Samples were taken by exploratory method. Data collection techniques consisted of observation, interviews, and documentation. The study revealed that there are 22 species, consisting of 9 genera and 2 types of orchids, namely natural orchids and cross orcids in sample areas. The 6 from 9 genera was natural orchids and it has 6 species, namely Arachnis flos-aeris, Arundina graminifolia, Bromheadia finlaysoniana, Spathologttis plicata, Dendrobium crumenatum, and Vanda douglas. Meanwhile, there are 5 hybrid orchids found and it consist of 16 species, named Aeridachnis apple-blossom, Aranda christine-alba, Phalaenopsis amabilis, Dendrobium blue-angel, D. caesar, D. eddy-djaya, D. haseltii, D. liberty-white, D. mangosteen, D. pink-stipe, D. popeye, D. sonia-white, D. valentine, D. white-dragon-angel, Vanda tricolor, and V. orange-delight.  Key words: diversity; orchids; Musi Rawas.